Analysis of assessment models of software product labouriousness during the development of corporate information systems of engineering process - Невлюдов, Игорь Шакирович; Евсеев, Владислав Вячеславович; Милютина, Светлана Святославовна; Бортникова, Виктория Олеговна (Eastern-European Journal of Enterprise Technologies, 2012)
The article describes the results of study of assessment models of software products development from the point of view of their application in corporate information systems of engineering process. The main models COCOMO I, II, III and SLIM model were examined. The conclusion is that these models can be applied only to assess the laboriousness of software products on the final stage of the life cycle, which prevents the assessment of their cost during the designing of requirements specification. It should be noted that it increases the risk of "dead software product". Another risk is the failure to implement all the functions and changes of the code, as well as works with databases. The need for such changes may be caused by the amendment of the interface and functional of a software product, which can be added by a client after the approval of requirements specification